Determinan Putus Sekolah Anak Usia 7–18 Tahun: Peran Kemiskinan, Demografi, dan Anggaran Pendidikan di Kota Palembang - Ainisyah Azzahra; Suhel Suhel; Anna Yulianita (Jurnal Riset Ilmu Ekonomi, 2026)
the school dropout rate among children aged 7–18 years in Palembang City during the period 2014–2024. The study employs a quantitative approach using secondary time-series data obtained from the Statistics Indonesia (BPS), the Palembang City Education Office, and Regional Government Budget (APBD) documents. The analytical method applied is the Autoregressive Distributed Lag (ARDL) model, which is capable of capturing both short-run and long-run relationships among variables with different orders of integration and is particularly suitable for a relatively small sample size. The findings reveal that poverty, demographic factors, and education expenditure significantly influence the school dropout rate. In the long run, poverty emerges as the most dominant factor contributing to higher dropout rates, while an increase in the school-age population places additional pressure on the regional education system. Conversely, higher education expenditure contributes to reducing the dropout rate, although its effect is relatively smaller than that of poverty. These findings indicate that school dropout is a multidimensional issue shaped by household economic conditions, demographic dynamics, and the effectiveness of education policies. Therefore, efforts to reduce school dropout rates require an integrated policy framework that combines educational development, poverty alleviation strategies, and educational planning that is responsive to demographic changes.